Phyto-Pharmacological Aspects of Cucumis melo var. agrestis: A Systematic Review - Kapoor, Manish; Sharma, Chanchal; Kaur, Navneet; Kaur, Gurdeep; Kaur, Rupinder; Batra, Kajal; Rani, Jyoti (Pharmacognosy Reviews)
Cucumis melo var. agrestis, belongs to the family Cucurbitaceae, is commonly known as wild melon, wild musk, small gourd, kachri or chibber. It is annual climber, monoecious, plant having thin stemmed and fruit with thin mesocarp and tiny seeds. Fruit possess variability in various morphological aspects. All the essential nutrients are present in adequate amount, so it is usually consumed as vegetable. Fruits are used as cooling light cleanser or moisturizer for skin and first aid treatment for burns and abrasions. It also possesses stomachic, digestive, febrifuge, vermifuge properties and show antioxidant, analgesic, anti-inflammatory activity. In this review we gave all-purpose outline of phyto-pharmacological aspects of Cucumis melo var. agrestis.
Keywords: Phyto-pharmacological activity; Cucumis melo; Catechin; Wild melon; Kachri; Chibber